The Logic and Pragmatics of Connectors - Henning Nølke (Hermes, 1990)
A long tradition has used logic for the description of connectors and other linguistic formators. It is argued in this article that this in fact is not a good idea. After an analysis of the meaning of connectors, as they have been studied in linguistics, their formal function is scrutinized. It is shown that one ought to distinguish their iconic function, which is the only one studied by linguists so far, from their deictic function, which controls the search for their arguments. This result permits us to address the crucial question: Why has logic acquired such a predominant place in the study of natural connectors? What is the basis for this way of viewing their function? It is finally shown how the insights obtained in this analysis can be exploited for the examination of the formal aspects of other linguistic items.